THE MYTHS AND REALITIES OF BAYESIAN CHRONOLOGICAL MODELING REVEALED. Issue 2 (6th November 2017) - Hamilton, W. Derek; Krus, Anthony M.
Abstract : We review the history of Bayesian chronological modeling in archaeology and demonstrate that there has been a surge over the past several years in American archaeological applications. Most of these applications have been performed by archaeologists who are self-taught in this method because formal training opportunities in Bayesian chronological modeling are infrequently provided. We define and address misconceptions about Bayesian chronological modeling that we have encountered in conversations with colleagues and in anonymous reviews, some of which have been expressed in the published literature. Objectivity and scientific rigor is inherent in the Bayesian chronological modeling process. Each stage of this process is described in detail, and we present examples of this process in practice. Our concluding discussion focuses on the potential that Bayesian chronological modeling has for enhancing understandings of important topics. Abstract : En este artículo se reseña la historia de la modelización cronológica bayesiana en arqueología y se demuestra que en los últimos años arqueología americana ha experimentado un auge en su aplicación. La mayor parte de los análisis han sido desarrollados por arqueólogos que son autodidactas en el aprendizaje del método, ya que las oportunidades de formación en el análisis bayesiano son muy limitadas. Se explica cuáles son los errores más comunes en la aplicación de la modelización cronológica bayesiana, algunas de los cuales ya han sido señaladas en otros trabajos, que hemos encontrado al conversar con compañeros y en revisiones anónimas. La objetividad y el rigor científico resultan inherentes al proceso de modelización cronológica bayesiana. Se describe en detalle cada etapa de este proceso, presentando ejemplos de su puesta en práctica. Nuestra conclusión se centra en torno al potencial de este método para mejorar nuestra comprensión sobre temas de gran relevancia.